Physical Medicine and Rehabilitation Approach of Elderly with Atypical COVID-19 Symptoms - Widjanantie, Siti Chandra; Burhan, Erlina; Susanto, Agus Dwi (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
COVID-19 has affected the older population disproportionately. These patients are prone to have more severe COVID-19. Clinical manifestation of COVID-19 in the geriatric can be atypical and differs from the younger population. We report an 80-year-old male with atypical presentation of COVID-19. In this case report, we describe a COVID-19 patient with anorexia and gastrointestinal symptoms. We also describe the multidisciplinary aspect of physical medicine and rehabilitation management of the patient. Clinical manifestations in geriatric with COVID-19 can be atypical. Symptoms experienced may include anorexia and gastrointestinal tract symptoms. A multidisciplinary approach is needed to manage more seniors with COVID-19 and maximize their functional abilities.